A New Product with Formic Acid for Varroa jacobsoni Oud: Control in Argentina. I. Efficacy - Eguaras, Martin Javier (2008)
An organic product based on formic acid in a gel matrix was evaluated for use in Varroa control under autumnal climatic conditions in Argentina. Twenty colonies each received two gel packets with formic acid in two applications and numbers of falling mites were registered. After this treatment colonies received two other acaricides in order to compare efficacy. Average final efficacy in colonies treated with the organic product was 92% with a low variability. The gel matrix kept an adequate formic acid concentration inside the colonies with only two applications. This product is, therefore, a good alternative for Varroa control because it is organic, easy to use and presents a low variability in final efficacy between colonies. No queen, brood, or adult honeybee mortality was registered.